The Role of Sharia Banking and E-Commerce in the Development of Micro, Small and Medium Enterprises - Salsabila Sirtufillaili; Bambang Bambang (International Journal of Business and Quality Research, 2024)
Sharia Banks and e-commerce are believed to contribute significantly to developing micro, small, and medium enterprises (UKMKM) in Indonesia. This research aims to analyze the influence of Sharia Banks and E-Commerce on the development of MSMEs in Praya City, Central Lombok Regency, by using regression analysis with the help of Partial Least Squares (PLS) and using data from 116 MSME respondents. The findings in this research show that Islamic banks have a positive and significant influence on the development of MSMEs in Praya City. Apart from that, the conclusions of this research also show a positive and significant influence between the use of E-commerce technology and the development of MSMEs, such as increasing sales turnover and sales profits. This finding has implications for MSME actors in Praya City, namely that, in running their business, they should use an e-commerce platform to market their products to be widely known. Apart from that, perpetrators can utilize Sharia bank products to finance MSME businesses.